STRUCTURAL ANALYSIS AND MAPPING OF HISTORICAL TOMBS IN AHLAT DISTRICT (BITLIS, TURKEY) (Advances in Civil and Architectural Engineering, 2021)
Tombs are an important part of the architecture in the ancient civilizations. Ahlat is a district located in the Lake Van Basin and has hosted many civilizations with its rich historical texture, a large part of which consists of tombs. In this study, observational structural analyses were performed for fifteen different tombs in the Ahlat district. Because of the investigations carried out in the field, the geometrical locations of the ditches were determined and mapping was carried out for these tombs. Damages in the tombs caused by natural reasons were determined and information about the preservation measures to be taken was provided. Finite element models were created for two selected tombs with different architectural characteristics that may represent the other tombs. The study aimed at determining the seismic behavior of the tombs for which two selected tombs were analyzed. Monumental buildings for historical heritage should be preserved for the next generations, which is possible if they could be investigated for structural characterizations. This study sets an example in that direction. The traceability of such structures is crucial for interventions in the historical buildings, which will become more practical with the help of the observational forms.